INTEGRATING MODELS CHARACTER EDUCATION IN HISTORY LEARNING - Dyah Kumalasari (Yogyakarta State University, 2022)
This article is the result of the 3rd year research. The research was designed into two phases (three years). The first stage has obtained results in the form of identification of the method of learning History in high schools in Yogyakarta, as well as whether or not character education has been integrated into the learning process. Based on this identification, a model of integrating character education into history learning in high school was found and a limited trial was carried out at MAN 1 Yogyakarta. In the second year, the developed model was implemented in three selected schools, namely SMAN 9 Yogyakarta, SMAN 8 Yogyakarta, and SMAN 6 Yogyakarta. In the third year, the dissemination of research results was carried out through training and mentoring activities for history teachers who are members of the DIY Province history MGMP.The dissemination of the research results was carried out in several activities, namely: (1) inviting 100 history teachers who are members of the DIY provincial history MGMP; (2) participated as a co-speaker in an international seminar at the University of Indonesia with the theme